Why/How are Integrated Reporting Practices Adopted/Diffused? Evidence From Public Listed Companies in Sri Lanka - Nawarathna Liyanage Erandi Abeywardana; S.M. Ferdous Azam; Kevin Low Lock Teng (Asian Journal of Business and Accounting, 2023)
Manuscript type: Research paper Research aims: This study explores the factors affecting and the internal mechanisms employed by companies to manage their integrated reporting practices. Design/Methodology/Approach: The qualitative study is conducted through semi-structured interviews with 15 officers responsible for the integrated reporting practices of public listed companies in Sri Lanka. Research findings: The study found that relative advantage, compatibility, complexity, trialability, and observability affect the adoption of integrated reporting practices. Under the internal mechanism, it was found that sustainability reporting helped the adoption, and companies used their own ways to collect and manage information. Despite the companies’ duration of practice, the constellations of structures, cultures, and reporting practices with which integrated reporting is managed change within the companies. Furthermore, the study showed the success stories of integrated reporting. Theoretical contribution/Originality: The study is the first South Asian and emergent market study to identify the enablers of integrated reporting by employing the diffusion of innovation theory as the theoretical foundation and internal mechanism. Practitioner/Policy implication: This study provides insight into the dynamic processes that operate within the framework of the organisational change that has taken place from this perspective and demonstrates how integrated reporting can be incorporated into the organisational change process. The experience of these organisations allows others that intend to embrace integrated reporting to choose the optimal way to implement it and use integrated reporting. Research limitations/Implications: Although much effort was taken to ensure that the study comprised successful IR businesses that displayed best practices in IR, this research study was confined to a small number of 15 public listed companies who participated.